PEMENFAATAN SUMBER DAYA ADAT DAN MINAT KUNJUNGAN WISATAWAN DALAM MENINGKATKAN EKONOMI DESA WOLOGAI TENGAH - Tola, Damianus; Amrin, Sayful; Hoban, Nong (Program Studi Ekonomi Pembangunan Universitas Flores, 2025)
This study aims to determine the utilization of indigenous resources and tourist interest in improving the economy of Central Wologai Village. Data collection was conducted by distributing questionnaires. The researchers selected 100 respondents using a proposed random sampling technique. The analysis tool used was simple regression analysis, processed using SPSS.21. The r-value of 0.569 was obtained from 25 questionnaire items, which was deemed valid. The reliability test showed a Cronbach's Alpha value of 0.839, indicating a significance level of 0.05. A Cronbach's Alpha value of 0.569 is greater than the r-value, indicating that the questionnaire items are considered reliable and categorized as good. The results of the study, with a constant value of 0.487, indicate that the variables of indigenous resource utilization and tourist interest have changed, indicating a significant relationship between the economy of Central Wologai Village. The correlation analysis showed an R-square value of 0.608, indicating that the contribution of the variables of customary resource utilization and tourist interest to the village's visit was 60.8%. It was concluded that customary resource utilization and tourist interest can significantly support the village economy.